A review of the influence of treatment strategies on antibiotic resistant bacteria and antibiotic resistance genes. (May 2016) - Sharma, Virender K.; Johnson, Natalie; Cizmas, Leslie; McDonald, Thomas J.; Kim, Hyunook
Abstract: Antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARG) in the aquatic environment have become an emerging contaminant issue, which has implications for human and ecological health. This review begins with an introduction to the occurrence of ARB and ARG in different environmental systems such as natural environments and drinking water resources. For example, ARG or ARB with resistance to ciprofloxacin, sulfamethoxazole, trimethoprim, quinolone, vancomycin, or tetracycline (e.g., tet (A), tet (B), tet (C), tet (G), tet (O), tet (M), tet (W), sul I, and sul II) have been detected in the environment. The development of resistance may be intrinsic, may be acquired through spontaneous mutations ( de novo ), or may occur due to horizontal gene transfer from donor bacteria, phages, or free DNA to recipient bacteria. An overview is also provided of the current knowledge regarding inactivation of ARB and ARG, and the mechanism of the effects of different disinfection processes in water and wastewater (chlorination, UV irradiation, Fenton reaction, ozonation, and photocatalytic oxidation). The effects of constructed wetlands and nanotechnology on ARB and ARG are also summarized. Highlights: Prevalence of ARB and ARG in rivers, lakes, surface water, wastewater, and sludge. Mechanism of resistance include horizontal gene transfer from donor bacteria. Chlorine and advanced oxidation processes inactivate ARB and ARG significantly. Flow pattern of the constructed wetlands governs removal of ARB and ARG. Nanoparticles have a role in investigating mechanism of transfer of ARG from genera.